Antiproliferation for Breast Cancer Cells by Ethyl Acetate Extract of Nepenthes thorellii x (ventricosa x maxima) - Ou-Yang, Fu (Int J Mol Sci, 2019)
Extracts from the Nepenthes plant have anti-microorganism and anti-inflammation effects. However, the anticancer effect of the Nepenthes plant is rarely reported, especially for breast cancer cells. Here, we evaluate the antitumor effects of the ethyl acetate extract of Nepenthes thorellii x (ventricosa x maxima) (EANT) against breast cancer cells. Cell viability and flow cytometric analyses were used to analyze apoptosis, oxidative stress, and DNA damage. EANT exhibits a higher antiproliferation ability to two breast cancer cell lines (MCF7 and SKBR3) as compared to normal breast cells (M10). A mechanistic study demonstrates that EANT induces apoptosis in breast cancer cells with evidence of subG1 accumulation and annexin V increment. EANT also induces glutathione (GSH) depletion, resulting in dramatic accumulations of reactive oxygen species (ROS) and mitochondrial superoxide (MitoSOX), as well as the depletion of mitochondrial membrane potential (MMP). These oxidative stresses attack DNA, respectively leading to DNA double strand breaks and oxidative DNA damage in γH2AX and 8-oxo-2′deoxyguanosine (8-oxodG) assays. Overall these findings clearly revealed that EANT induced changes were suppressed by the ROS inhibitor. In conclusion, our results have shown that the ROS-modulating natural product (EANT) has antiproliferation activity against breast cancer cells through apoptosis, oxidative stress, and DNA damage.